Towards a Service-Oriented Capability-Driven Selection of Cots Business Software - Kluge, Rolf; Ludwig, André; Franczyk, Bogdan; Maciaszek, Leszek (Advanced Information Technologies for Management – AITM 2009, 2009)
This paper provides an insight to the in-progress research on a service-oriented capability-driven approach that supports the selection of COTS business software. Service-oriented means that the concepts of service-orientation (i.e. models, methods and techniques) are adopted in the selection and that COTS business software is perceived as service provider having a set of service capabilities. Capability-driven means that the selection process is driven by matching required service capabilities of service consumer with provided capacities and abilities of COTS business software.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 133-145